Swear words among young learners: A case study of the elementary students - Maria Fe Suganob-Nicolau (Indonesian JELT, 2016)
This case study examines the usage of swear words among young learners. It aims to find out the most frequently used swear words, the intense emotions that triggered the participants to swear, the strategies used to tone down the swear words, and the contributors to learning how to swear. A combination of quantitative (Likert scale survey, open-ended survey, and data elicitation from drawings,) and qualitative (interview) studies was conducted among the 109 elementary students from school A. The findings revealed that the most frequently used swear words were related to intellectual based terms and religion; anger was the primary reason for the young learners to swear to someone; the use of acronyms was commonly explored to tone down the offensiveness of the swear words, and moms were the highest contributors for the young learners to learn how to swear. Despite the limitations of the data elicitation, the instrument offered a richer data in comparison with the two other quantitative instruments (Likert scale survey and open-ended survey). It did not only present the emotions, toning down strategies, contributors, categories and variations but it also revealed the locations and situational instances where the swear words were used. Interview, on the other hand, was valuable to support the qualitative findings related to emotions and reasons for toning down strategies whereas other findings can be quantified using the frequencies presented in the quantitative instruments. Moreover, the findings also discovered that some swear words under study such as OMG, Oh my God, or gosh were not considered as swear words since they were mainstream words in this particular study.